Pelatihan Skrining Status Gizi dan Edukasi Kesehatan untuk Cegah Malnutrisi pada Remaja - Tampubolon, Nurhannifah Rizky; Erika, Erika; Tampubolon, Masrina Munawarah; Suci, Wice Purwani; Putri, Syeptri Agiani (Unri Conference Series: Community Engagement, 2024)
Today's teenagers grow up in an environment that puts them at risk of experiencing micronutrient deficiencies. One of the causes is their limited knowledge, which affects their decision-making when it comes to choosing nutritious food from the options available to them. To address these issues, nutritional status screening training and health education are necessary to prevent malnutrition among adolescents. This community service aims to increase health knowledge among teenagers and improve their skills in screening for nutritional status. The method used is training through the provision of health information related to balanced nutrition, reproductive health, and the nutritional needs of teenagers. After the material is delivered, the program continues with a simulation involving weighing, measuring height, and calculating body mass index. This activity involved 20 teenagers in Limbungan Baru Village, Pekanbaru City. The results showed an increase in the percentage of teenagers with a good level of knowledge, from 15% before the training to 75% after the training. Adolescents who have received training need to be involved in posyandu (community health center) activities so that their skills are maintained and can contribute to increasing community independence in maintaining health status.